Morphological association between muscle attachments and ossification sites in the late cartilaginous skull of tuatara embryos. (29th April 2022) - Zhang, Zitong; Yaryhin, Oleksandr; Koyabu, Daisuke; Werneburg, Ingmar
Abstract: During development, the embryonic cartilaginous skull in most vertebrates is partially replaced by bones with endochondral and perichondral ossifications. Muscle attachments are thought to influence the patterns of ossification and, hence, the differentiation of the skull. To investigate the association between muscle attachments and early ossifications of reptilian embryos, we conducted digital 3D reconstructions of the cranium, the head, and the neck musculature from a histological section series of a late term embryonic tuatara, Sphenodon punctatus, with a total body length of 52 mm. As the sole living rhynchocephalian species, it is an important outgroup in comparative studies of squamate evolution. We found that head and neck muscles are largely associated with early ossification of the basal plate and the palatoquadrate, and with three other ossifications in an older specimen with a total body length of 72 mm. These results suggest that tensile forces resulting from embryonic muscle contraction are largely, but not exclusively, correlated with the area of endochondral ossification in the chondrocranium and palatoquadrate in tuatara. Beyond little‐known genetic factors, the complexity of chondrocranial architecture, the progress of its development, and the effect of multiple muscle transmitting forces in the chondrocranium must be considered to provide a more comprehensive discussion of the mechanical properties of the embryonic skull. Abstract : In this study, the authors used conventional morphological description and digital 3D reconstruction to study muscle‐cartilage interaction and endochondral ossification in the chondrocranium and the palatoquadrate of embryos of Sphenodon punctatus .